2021
DOI: 10.3390/molecules26113301
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanodelivery of Green Tea Catechins to Enhance the Anticancer Activity

Abstract: Cancer is one of the leading causes of death globally. A variety of phenolic compounds display preventative and therapeutic effects against cancers. Green teas are rich in phenolics. Catechins are the most dominant phenolic component in green teas. Studies have shown that catechins have anticancer activity in various cancer models. The anticancer activity of catechins, however, may be compromised due to their low oral bioavailability. Nanodelivery emerges as a promising way to improve the oral bioavailability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 183 publications
(179 reference statements)
0
20
0
Order By: Relevance
“…Quercetin can prevent and treat different types of cancer by acting as an apoptosis inducer or growth inhibitor [ 49 ]. Additionally, catechins showed anticancer activity against various types of cancer through regulation of inflammation, proliferation, cell cycle, oxidative stress, and metastasis processes [ 50 ]. So, the isolation of the phenolic fraction of these biologically active compounds from leaf, flower, and stem parts of commercially available artichoke ( C. scolymus L.) was a must for further assessment of their nanoformulations.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin can prevent and treat different types of cancer by acting as an apoptosis inducer or growth inhibitor [ 49 ]. Additionally, catechins showed anticancer activity against various types of cancer through regulation of inflammation, proliferation, cell cycle, oxidative stress, and metastasis processes [ 50 ]. So, the isolation of the phenolic fraction of these biologically active compounds from leaf, flower, and stem parts of commercially available artichoke ( C. scolymus L.) was a must for further assessment of their nanoformulations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous nanoformulations of epicatechin gallate and epicatechin digallate have been prepared and established their anticancer potential against ovarian, prostate, colon, and breast cancers. PLGA nanoparticles and solid lipid nanoparticles of epicatechin digallate of green tea have been reported for their antiproliferative effects using in vitro and in vivo models ( Jiang et al, 2021 ). Epicatechin gallate had been evaluated against ovarian cancer cell lines such as SKOV-3, OVCAR-3, OVCA-433, and HEY human ovarian cancer cell lines using in vitro cytotoxicity studies ( Huh et al, 2004 ; Spinella et al, 2006 ; Chen et al, 2011 ; Singh et al, 2011 ; Yan et al, 2011 ; Huang et al, 2020 ; Qin et al, 2020 ).…”
Section: Nanomaterials and Semi-synthetic Analogs Of Natural Anti-er ...mentioning
confidence: 99%
“…It is generally used in cisplatin-resistant ovarian cancer. Jiang et al reported the PLGA-loaded nanoparticles of catechins including theaflavin-3,3ʹ-digallate and epicatechin-3,3ʹ-digallate and evaluated their anticancer potential against ovarian and breast cancer ( Jiang et al, 2021 ). Youying et al established that it has an apoptotic effect on ovarian cancer cell lines and causes arrest in the G2 phase via upregulating p53 protein expression ( Tu et al, 2016 ).…”
Section: Nanomaterials and Semi-synthetic Analogs Of Natural Anti-er ...mentioning
confidence: 99%
“…Solubility the bioavailability of phytochemicals like GTCs. They can also achieve targeted delivery when modified with targeting molecules [25][26][27], and also can improve therapeutic efficacy by enhancing the bioavailability and stability and significantly enhance the anti-skin cancer efficacy and stability of EGCG and GTCs, by protecting the GTC's degradation in tissue's microenvironment [28][29][30][31]. Recently vesicular nanocarriers, mainly transfersomes or deformable liposomes, have gained much attention owing to their tailored membrane functionalities, including selfadaptable, ultra-flexible, more elastic in nature and high radius of curvature etc., which were found suitable for effective skin delivery [32,33].…”
Section: Introductionmentioning
confidence: 99%